Cell-free transcription directed by the 422 adipose P2 gene promoter: activation by the CCAAT/enhancer binding protein. - Cheneval, D (1991)
Previous investigations have shown that CCAAT/enhancer binding protein (C/EBP) can function as a trans-activator of the promoters of several adipocyte-specific genes--i.e., the 422 adipose P2 (422/aP2), stearoyl-CoA desaturase 1 (SCD1), and glucose transporter 4 (GLUT4) genes, in 3T3-L1 mouse preadipocytes. We now describe a cell-free system prepared from nuclei of 3T3-L1 cells that carries out transcription directed by these promoters. To measure transcript formation, we employed a polymerase chain reaction-assisted analysis. Nuclear extract from 3T3-L1 adipocytes that express C/EBP supports a higher rate of transcription of chimeric 422(aP2) promoter-chloramphenicol acetyltransferase (CAT) reporter gene constructs than nuclear extract from preadipocytes that lack C/EBP. A competitor oligonucleotide containing the C/EBP binding site sequence and antibodies raised against C/EBP inhibit transcription directed by the 422(aP2) promoter. The factor limiting transcription by nuclear extract from preadipocytes appears to be C/EBP, since recombinant C/EBP (rC/EBP) markedly activates transcription of the 422(aP2) promoter-CAT gene with preadipocyte extract but not with adipocyte extract. rC/EBP also activates cell-free transcription of SCD1 promoter-CAT and GLUT4 promoter-CAT chimeric genes. Point mutations within the C/EBP binding site in the 422(aP2) promoter markedly decrease transcription activated by rC/EBP. Consistent with activation by cAMP of the 422(aP2) promoter in intact preadipocytes, cAMP-dependent protein kinase activates transcription through this promoter with the cell-free system, this effect being independent of C/EBP. Thus, regulation of transcription directed by the 422(aP2) promoter in the cell-free system resembles that which occurs in intact 3T3-L1 cells.